2016
DOI: 10.1007/s10695-016-0225-3
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of Bax1 and Bax2 genes of Ctenopharyngodon idellus and evaluation of transcript expression in response to grass carp reovirus infection

Abstract: Multidomain proapoptotic Bcl-2-associated X (Bax) protein is an essential effector responsible for mitochondrial outer membrane permeabilization, resulting in cell death via apoptosis. In this study, two Bax genes of grass carp (Ctenopharyngodon idellus), designated as CiBax1 and CiBax2, were isolated and analyzed. The obtained CiBax1 cDNA is 2058 bp long, with a 579 bp open reading frame (ORF) coding a protein of 192 amino acid residues. The full-length cDNA of CiBax2 is 1161 bp, with a 618 bp ORF coding 205 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…Therefore, it is not surprising that the mRNA expression level of Bid was up-regulated at the late stage of infection. Similar expression pattern was also observed in other pro-apoptotic genes in grass carp [19,32]. Moreover, the dynamic changes of GCRV copy number in infected grass carp was detected in our previously study [33].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Therefore, it is not surprising that the mRNA expression level of Bid was up-regulated at the late stage of infection. Similar expression pattern was also observed in other pro-apoptotic genes in grass carp [19,32]. Moreover, the dynamic changes of GCRV copy number in infected grass carp was detected in our previously study [33].…”
Section: Discussionsupporting
confidence: 84%
“…In addition, the expression profiles of CiCaspase-9 and CiCaspase-3 in liver and intestine after GCRV infection were also examined. As shown in Figure 4G, 4H, 4I, and 4J, the expression profiles of CiCaspase-9 and CiCaspase-3 were the same as we described previously [19]. To be specific, expression level of CiCaspase-9 and CiCaspase-3 in intestine was decreased at first upon GCRV stimulation and then began to up-regulate significantly around 4 or 5 days post stimulation ( Figure 4G and 4H).…”
Section: Expression Analysis Of Cibid and Apoptosisrelated Genes Aftesupporting
confidence: 77%
See 1 more Smart Citation
“…Even though Sivakumar et al (2014) research is based on mammals, Eimon and Ashkenazi (2010) approved of such proteins to be exist and have a same exact role in zebrafish. Wang et al (2016) also reported the presence of BAX in grass carp (Ctenopharyngodon idellus).…”
Section: The Effect Of K 2 Cr 2 O 7 In Decreasing the Amount Of Pgcsmentioning
confidence: 94%